Gabapentin drug interactions in water and aqueous solutions of green betaine based compounds through volumetric, viscometric and interfacial properties - Elaheh Janbezar; Hemayat Shekaari; Mohammad Bagheri (Scientific Reports)
Abstract Betaine as a bio-based surfac﻿tant, has been found in a variety of natural sources. Betaine improves drug absorption, protect drugs from degradation, and enhance the performance of various therapeutic and hygiene products. To investigate the interactions between gabapentin (an antiepileptic drug) and betaine-based compounds, series of experiments were conducted at 298 K. These experiments involved volumetric, viscometric, and surface tension measurements of aqueous solutions containing gabapentin and various betaine-based compounds, including betaine, betaine octyl ester chloride ionic liquid and betaine-urea deep eutectic solvent (molar ratio of 1:2). Additionally, the Conductor like Screening Model (COSMO) method were employed to gain further insights into molecular interactions governing these systems. The volumetric studies revealed that the standard partial molar volumes V 0 φ of the betaine-based compounds increased with increasing gabapentin concentration, suggesting significant solute-solvent interactions. The apparent specific volume (ASV) and the hydration number (n H) for gabapentin in the examined systems were calculated. The analysis of the obtained ASV and n H values indicated that gabapentin exhibits a bitter taste in aqueous deep eutectic solvent (DES) solutions and in the presence of betaine it gets most dehydrated. The viscosity measurements, analyzed using the Jones-Dole equation, yielded negative viscosity B-coefficient values for the betaine octyl ester chloride ionic liquid, suggesting its potential to enhance the drug-related properties of gabapentin. Surface tension measurements were used to determine the critical micelle concentration (CMC) of the betaine-based compounds and their related surface properties such as interface surface pressure ( $$Π$$ ), and Gibbs maximum excess surface concentration ( $${Γ _{\hbox{max} }}$$ ). The CMC values decreased with increasing gabapentin concentration, indicating enhanced micellization. The betaine octyl ester chloride ionic liquid exhibited the lowest CMC, suggesting its superior ability to form micelles. The results of this study suggested that the betaine-based compounds improve drug absorption, protect drugs from degradation, and enhance the performance of various therapeutic and hygiene products underscores their importance in both the pharmaceutical and industrial sectorsunds, particularly the betaine octyl ester chloride, may have the potential to improve the drug-related properties of gabapentin.